2015
DOI: 10.1097/mbc.0000000000000177
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of absorbable polysaccharide haemostats in wound healing

Abstract: Wound healing represents an ancient problem for humans, and various materials and methods have been tried for wound dressing. A dressing should protect against infection and shorten healing; moreover, it should not cause tissue damage and should be nonallergenic, cost effective and easy to apply. These are characteristics that may be found in herbal extracts. An absorbable polysaccharide haemostat (APH) is a plant-based haemostatic agent. We aimed to evaluate the effect of APH on wound healing. A total of 24 W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…In their study examining the effect of polysaccharide hemostatic agents on wound healing in a rat model, Sonmez et al found that the collagen type I/III ratio, inflammatory score, fibroblast density, and vascular proliferation were significantly higher in the polysaccharide hemostatic agent group than in the saline group. Wound contraction rates were also significantly higher in the polysaccharide hemostatic agent group than in the control group 15 …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In their study examining the effect of polysaccharide hemostatic agents on wound healing in a rat model, Sonmez et al found that the collagen type I/III ratio, inflammatory score, fibroblast density, and vascular proliferation were significantly higher in the polysaccharide hemostatic agent group than in the saline group. Wound contraction rates were also significantly higher in the polysaccharide hemostatic agent group than in the control group 15 …”
Section: Discussionmentioning
confidence: 83%
“…Prolonged bleeding and excessive exudation can delay wound healing. Polysaccharide hemostatic agents provide hemostasis, absorb excessive exudation, and cover the entire wound surface 15 . In their study examining the effect of polysaccharide hemostatic agents on wound healing in a rat model, Sonmez et al found that the collagen type I/III ratio, inflammatory score, fibroblast density, and vascular proliferation were significantly higher in the polysaccharide hemostatic agent group than in the saline group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O creme de dexpantenol a 5% é amplamente utilizado, pois indica melhorias na cicatrização de feridas (Heise et al, 2012;Oguz et al, 2015;Ulger et al, 2014), visto que penetra facilmente na pele em concentrações locais elevadas. Os efeitos mais significativos de formulações com dexpantenol a 5% incluem a estimulação da epitelização, granulação e o alívio de prurido (Ebner et al, 2002 (Das, 2013;Diegelmann e Evans, 2004;Ebner et al, 2002;Khoshneviszadeh et al, 2014;Sonmez et al, 2015). Sugere-se que esta atividade estimuladora de fibroblastos da derme no grupo da planta estudada é devido à presença de taninos hidrolisáveis (Bueno et al, 2014).…”
Section: Resultsunclassified
“…(Melchor et al, 2001;Bandaranayake, 2002;Marrero et al, 2006;Berenguer et al, 2006;De-Faria et al, 2012 A cicatrização de feridas é um processo dinâmico, interativo e iniciado em resposta a uma injúria (Guo e Dipietro, 2010), cujo objetivo é restaurar a continuidade anatômica efuncional do tecido, sendo essencial para a manutenção da integridade do organismo (Barbul,1990;Broughton et al, 2006;Thornton et al, 1997 (Fernandez et al 2002, Perera et al 2010. Fernandez et al (2002) (Das, 2013;Diegelmann e Evans, 2004;Ebner et al, 2002;Khoshneviszadeh et al, 2014;Sonmez et al, 2015). Sugere-se que esta atividade estimuladora de fibroblastos da derme no grupo da planta estudada é devido à presença de taninos hidrolisáveis (Bueno et al, 2014).…”
Section: Análise Estatísticaunclassified